THE EFFECT OF RED SPINNING VEGETABLES ON HEMOGLOBIN LEVELS OF HEMOGLOBIN POSITION IN PONCOKUSUMO DISTRICT, MALANG REGENCY - Ervin Rufaindah; Patemah Patemah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Anemia in the puerperium is a continuation of anemia suffered during pregnancy, which causes many complaints for mothers and reduces work presentations, both in daily homework and in caring for babies. Data from the 2012 Household Health Survey (SKRT) states that the prevalence of anemia in children under five is 40.5%, pregnant women is 50.5%, postpartum women is 45.1. The purpose of this study was to determine the effect of red spinach on hemoglobin levels in postpartum mothers in Poncokusumo District, Malang Regency. The design of this study was a quasi-experimental design using the one group pretest posttest design research using an accidental sampling technique of 30 people. The data used are primary and secondary data. The data were analyzed using the paired t test analysis. Results: From the results of the research with the statistical test results, the Asym sig (2-tailed) value of 0.000 is less than 0.05, it can be concluded that there is an effect of red spinach on increasing hemoglobin levels in postpartum mothers in Poncokusumo District, Malang Regency. It is hoped that it can activate postpartum mothers by collaborating with local midwives to encourage postpartum mothers to consume red spinach every day or other foods that can increase hemoglobin levels